Effect of cold-water immersion on elbow flexors muscle thickness after resistance training - Matos, F.; Neves, E. B.; Rosa, C.; Reis, V. M.; Saavedra, F.; Silva, S.; Tavares, F.; Vilaça-Alves, J. (The Journal of Strength and Conditioning Research, 2018)
Cold-water immersion (CWI) is commonly applied to speed up the recovery process after exercise. Muscle damage may induce a performance reduction and consequence of the intramuscular pressure induced by the muscular swelling. The aim of the study was to verify the CWI effects on muscle thickness (MT) behavior of the elbow flexors after a strength training (ST) protocol. Eleven men were submitted to an ST, performed in 2 different weeks. In one of the weeks, subjects experienced a passive recovery. In the other, subjects were submitted to a CWI (20 minutes at 5-10° C). Ultrasound (US) images were taken before, after, as well as 24, 48, and 72 hours after exercise, to evaluate the MT. Muscle thickness in both exercise arm (EA) and control arm (CA) was significantly higher 48 and 72 hours after exercise when subjects were submitted to a passive recovery compared with the CWI (p = 0.029, p = 0.028, p = 0.009, and p = 0.001, 48 hours, 72 hours, EA, and CA, respectively). When each arm was analyzed with or without using CWI individually, significantly higher MT was observed in the EA with CWI: before exercise in relation to 72 hours after exercise (p = 0.042) and after exercise in relation to the other measurements (p = 0.003, p = 0.003, p = 0.038, and p < 0.0001, before exercise and 24, 48, 72 hours after exercise, respectively). The evaluation of MT by US provides evidence that CWI after ST (and 24 hours after exercise) may reduce muscle swelling in the postexercise days when compared with a passive recovery. Seems to be a paradox between the uses of CWI for an acute reduction of muscle swelling.